Analysis of public policy-making for civil service reform in Egypt: law 18/2015 - El Sayed, Sarah Nasr Eldeen Ibrahim (AUC Knowledge Fountain, 2016)
This research aims at analyzing the policy-making process for civil service reform in Egypt with a focus on the Civil Service Law no. 18/2015, its rejection in parliament, and later the proposition of a new draft-law to replace it in parliament. It deals with policies mainly in the form of laws and bylaws, as it adopts the legal definition of policy. Although there is a near consensus amongst scholars on the dire need for civil service reform in Egypt, and although the new proposed civil service law 18/2015 was perceived as one main avenue towards the much needed reform, yet it was the only decree-law to be rejected by the parliament amongst 340 others. The main research question is how can the public policy-making process for civil service reform in Egypt be better analyzed and be understood using the new proposed Civil Service Law 18/2015 as a case study? The study begins with the presentation of literature on international experiences of civil service reform policy-making. It reviews studies of policy-making for civil service reform in Egypt, along with a number of studies on the theoretical frameworks that analyze the policy-making process. For the case study, it studies the policy-making process for the Civil Service Law (CSL) no. 18/2015 beginning with its drafting by the Ministry of Planning, to its rejection by parliament, followed by the process of formulating a new draft law on civil service, as the research was nearing completion. Additionally, the research analyzes the concerns of government, members of parliament (MPs), syndicates and federations regarding the civil service law making process. The methodology used by the study relied on the conduction of semi-structured purposive interviews with a sample of the law drafters, the parliament members, and the representatives of syndicates and federations. The findings were analyzed according to the input-output model and punctuated equilibrium theory. Numerous recommendations to reform the civil service policies in Egypt were derived from the field study including: the need for government having a clear vision, training employees, reforming the wage structure, and more importantly following a more participatory method of policy-making, and promoting the law through public media campaigns.